Eksploitasi Anak pada Film Surat Kecil untuk Tuhan - Dwinanda Gita Safitri; Kartika Suci Lestari Parhusip (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
Exploitation is a discriminatory attitude. One of the film which is about explotation is Surat Kecil Untuk Tuhan. This study aims to analyze how the reality of exploitation described in Surat Keci Untuk Tuhan. This research is qualitative, using social media construction theory and using the constructivist paradigm. This research uses Charles Sanders Pierce’s semiotic analysis to see the reality of exploitation which consist of stages of signs, objects, and interpretants, then by dividing the signs into qualisign, sinsign and legisign. The results showed that explotation that occurred in this film is pshysical exploitation, social exploitation and sexual exploitation.